2014
DOI: 10.1002/cbic.201402241
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Functional, and Spectroscopic Characterization of the Substrate Scope of the Novel Nitrating Cytochrome P450 TxtE

Abstract: A novel cytochrome P450 enzyme TxtE was recently shown to catalyze the direct aromatic nitration of L-tryptophan. This unique chemistry induced us to ask whether TxtE could serve as a platform for engineering new nitration biocatalysts, as a replacement for current harsh synthetic methods. As a first step toward this goal and to better understand the wild-type enzyme, we have obtained high-resolution structures of TxtE in its substrate-free and substrate-bound forms. We have also screened a library of substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
108
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(120 citation statements)
references
References 25 publications
12
108
0
Order By: Relevance
“…350,351 Screening of a library of substrate analogs in which the amino, carboxylate, and indole moieties were all modified revealed molecular determinants for substrate binding and catalysis. 350 The TxtE substrate must possess an indole ring and accepts only slight modifications to this substructure. Furthermore, the amino and carboxylate groups are essential, and act as a hydrogen bond donor and acceptor, respectively, to properly position the indole moiety in the active site.…”
Section: N–o Bond Forming Enzymesmentioning
confidence: 99%
“…350,351 Screening of a library of substrate analogs in which the amino, carboxylate, and indole moieties were all modified revealed molecular determinants for substrate binding and catalysis. 350 The TxtE substrate must possess an indole ring and accepts only slight modifications to this substructure. Furthermore, the amino and carboxylate groups are essential, and act as a hydrogen bond donor and acceptor, respectively, to properly position the indole moiety in the active site.…”
Section: N–o Bond Forming Enzymesmentioning
confidence: 99%
“…274 Subsequent studies have also shown that TxtE has tolerance for certain alternate substrates. 302 This reaction has been shown to require NO (generated by TxtD from arginine) and O 2 in addition to L-Trp, with electrons provided by a competent redox partner system from NAD(P)H (e.g. spinach Fdx/FdR) in order to generate a ferric peroxynitrite species as the reactive intermediate.…”
mentioning
confidence: 99%
“…Mutation of the conserved axial cysteine to serine enabled further novel catalysis, C-H amination (88) and N-H insertion (89). Lastly, a cytochrome P450 oxidase was discovered that catalyzed nitration of tryptophan derivatives (90).…”
Section: Wwwannualreviewsorg • Biocatalysis: a Status Reportmentioning
confidence: 99%